SPECIFIC FEATURES OF ARRESTING PROPERTY IN CASES OF CORRUPTION CRIMES - Melkonyan, Davit (State and Law, 2022)
The article is dedicated to the seizure of property subject to confiscation during the investigation of corruption crimes. Based on an analysis of international documents, such as the FATF Recommendations, the UN Conventions, and the ECHR judgments, the author concludes that at the initial stage of the investigation of corruption crimes, the amount of seized property may exceed the amount of property mentioned in the indictment, provided there are sufficient grounds that as a result of the investigation, the amount of property subject to confiscation will increase unquestionably.
Keywords: seizure of property; corruption; confiscation; money laundering